Effects of host species, environmental filtering and forest age on community assembly of ectomycorrhizal fungi in fragmented forests. (December 2018) - Boeraeve, Margaux; Honnay, Olivier; Jacquemyn, Hans
Abstract: Understanding the assembly of biological communities in space and time is a major goal in community ecology. While most studies have focused on community assembly patterns in macro-organisms, there are comparatively few studies on micro-organisms. Here, we investigated how communities of ectomycorrhizal (EcM) fungi assemble in fragmented forests. We used a space-for-time substitution as an alternative for long-term studies to investigate variation in EcM fungal communities in three host species collected from 41 forest patches of different ages. Metabarcoding of root samples revealed that community composition was affected by a combination of host plant, soil variables, and forest age. While there were no clear effects of forest age on EcM fungal communities in early-successional tree species alder and hawthorn, forest age did affect the EcM fungal communities in hazel, which is typically associated with ancient forest. EcM fungal communities in early-successional species were affected mostly by soil conditions.